Waste Water Treatment Using Sequential Batch Reactor and Development of Microbiological Method for the Analysis of Relative Toxicity - Altaf, Muhammad Saqib; Ali, Tasneem Adam (Pakistan Journal of Nutrition, 2010)
Pharmaceutical industry is a very progressing sector in Pakistan with over 400 Pharmaceutical manufacturing in the country. The pharmaceutical industry in Karachi is discharging thousands of gallons of waste per day carrying with itself huge quantities of antibiotics, other pharmaceutical synthetics and solvents as its major constituents. These substances are not only harmful to the aquatic flora and fauna but may also contribute to development of resistance to antibiotics. We designed a sequential batch reactor (SBR) after a series of experiments. The effluent met the NEQS specifications after 21 days of treatment in the SBR. The changes in pH, BOD, COD, TDS, TSS, Ammonia levels, Oil and grease levels were found to be significant (p < 0.05).